ANALISIS KESALAHAN BERBAHASA PADA PENULISAN MEDIA LUAR RUANG DI DAERAH KOTA PADANG SIDIMPUAN UTARA - Elvina Sari Nasution; Sholatiah Lubis; Verdy Suryadi; Nikmah Sari Hasibuan (Jurnal Komposisi, 2020)
This study aims to: 1) explain the forms of Indonesian language errors in outdoor media writing in Padang Sidimpuan Utara City, 2) errors in the use of foreign elements and 3) find out the suitability of research results with Indonesian language teaching materials in junior high schools or the community environment. This research is a qualitative descriptive study with samples of outdoor media writing in Padang Sidimpuan Utara City. This research uses an interactive analysis model which includes four components, namely data collection, data reduction, data presentation, and data verification. The conclusions of this study are first, linguistic elements that occur language errors in outdoor media, namely errors in the aspect of using punctuation marks, especially periods (.), writing prepositions at, using o'clock and hours, and abbreviations. Second, the type of use of foreign language terms which are often combined with Indonesian. Second, the language is used simultaneously in every Indonesian word or phrase. Third, the results of this study can be adapted to teaching materials in Indonesian language subjects at the junior high school level, especially on spelling material and foreign terms (absorption elements).